Non-thermal plasma enhances growth and salinity tolerance of bok choy (Brassica rapa subsp. chinensis) in hydroponic culture - Veerana, Mayura; Ketya, Wirinthip; Choi, Eun-Ha; Park, Gyungsoon (Frontiers in Plant Science, 2024)
In this study, we aimed to examine the growth, physiological and biochemical status, and responses to salinity stress of bok choy (Brassica rapa subsp. chinensis) cultivated in a hydroponic system with a plasma-treated solution. Plasma gas generated using a cylindrical dielectric barrier discharge or air (control) was injected into Hoagland nutrient solution once a week for different durations (0, 5, and 10 min). After 4 weeks, the length of the shoots and roots, number of leaves, and dry weight of bok choy plants significantly increased in individuals grown with Hoagland solution treated with plasma gas for 10 min. An increase in dry weight of individual plants of approximately 80.5% was observed in plants in the plasma-treated group compared to those in a control group. The levels of chlorophyll, total soluble proteins, and nitrogen uptake were also significantly elevated in bok choy grown with plasma treated Hoagland solution. Moreover, when exposed to 20 mM NaCl, transcription of genes related to salinity stress tolerance-WRKY2, HHP3, and ABI1-was significantly upregulated, and plant length and leaf number were significantly increased, in the group grown with Hoagland solution treated with plasma gas for 10 min. Level of H2O2 was significantly elevated in the treated nutrient solutions. In plants grown with the treated nutrient solution, intracellular NO was highly detected in the cell division and elongation zone of roots. Our findings suggest that plasma treatment of nutrient solutions in hydroponic culture systems may improve the growth, physiological and biochemical status, and tolerance to salinity stress in plants, and a crucial role of H2O2 generated in the treated nutrient solutions may play in this improvement.